HAND MASSAGE TITIK PERICARDIUM 6 (P6) TERHADAP PENURUNAN NYERI PADA PASIEN PREOPERASI BEDAH SARAF : HAND MASSAGE P6 ON PAIN REDUCTION INNEUROSURGERY PREOPERATIVE PATIENS - Patrya Setya Kesuma; Sarka Ade Susana; Yusniarita Yusniarita (Quality: Jurnal Kesehatan, 2026)
Pain experienced by patients before neurosurgery surgery becomes a problem during intraoperative, namely the emergence of neurogenic shock and increased use of anaesthetic drugs that can have the effect of post-anesthesia sedation and increased intracranial pressure. Hand massage is able to reduce pain perception by providing stimulation to the nerves so as to reduce the perception of pain transmitted to the brain. The purpose of this study was to determine the effect of P6 hand massage on pain reduction in neurosurgery preoperative patients at Kanjuruhan Hospital Malang. This research method uses a quasy-experiment pretest-posttest research design with control group. The sampling technique used total sampling technique involving 30 respondents. Data analysis using Wicolxon test and Mann Whitney test. The research instrument used the Numeric Rating Scale pain scale. Data collection was carried out on 13 February - 23 March 2024 at Premedication Anesthesia Installation Kanjuruhan Hospital Malang. A statistically significant difference in pain levels was observed before and after the hand massage intervention in both groups, as indicated by a p-value of 0.028 (p < 0.05) and There was a significant difference in the reduction of pain scale scores, with a p-value of 0.008 (p < 0.05). The conclusion of the study is that there is a significant effect between hand massage P6 on reducing pain in neurosurgical preoperative patients.